Digital Transformation for Effective Arabic Learning - Rahmat Hidayat; Melisa Rezi; Muh Akhyar Kadir; Nur Shofa Ulfiyati (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. Arabic language learning faces challenges in engaging students due to the traditional methods employed. With the advent of digital transformation, there is potential to enhance this learning experience. This study explores the integration of digital tools, specifically the Canva application, into Arabic language education to increase student interest and engagement. Purpose. The primary aim of this research is to evaluate the effectiveness of using the Canva application as a digital tool to enhance students' interest in learning Arabic. Method. This study employs a qualitative research methodology. Data was gathered through descriptive analysis, focusing on the experiences and outcomes of using Canva in Arabic language learning. The research involved direct observations and interviews with Arabic language teachers and students to gather relevant insights. Results. The findings indicate that the use of Canva significantly enhances the learning experience. Students showed increased interest and engagement in Arabic lessons when digital media, like Canva, was used. Teachers reported that Canva's interactive and visually appealing templates made lessons more enjoyable and easier to understand for students. The application facilitated better retention of vocabulary and concepts through creative visual aids. Conclusion. Integrating digital tools like Canva into Arabic language learning can substantially improve student engagement and interest. The positive response from both students and educators suggests that such tools are effective in modernizing traditional learning methods. This study underscores the importance of digital transformation in educational practices and encourages the adoption of innovative teaching aids to enhance learning outcomes.